Berani berprinsip - Khalid Samad, 1957- (Petaling Jaya, Selangor : Ilham Books, 2014)
On political culture in Selangor, Malaysia.
Koleksi sumbangan : Dr. Syaidatun Nazirah Abu Zahrin.
Keywords: Political culture -- Selangor -- Malaysia; Malaysia -- Politics and government